Implementation of Nursing Care for Mrs. K with Stage IIC Ovarian Cancer Post Hysterectomy Bilateral Salpingo Oophorectomy (HTSOB) in Fulfilling the Need for Pain Comfort with Distraction Techniques in the Treatment Room on the Second Floor of the Iman Sudjudi Pavilion, Gatot Soebroto Army Hospital, Jakarta - Kamilah, Lilis (STIKes RSPAD RSPAD Gatot Soebroto, 2021)
Ovarian cancer is a malignant tumor that develops from the ovaries and is often found in women aged 50 to 70 years. The prevalence of ovarian cancer in the world in 2020 was 313,959 cases while in Indonesia it was 14,896 cases. Patients treated in the treatment room on the 2nd floor of the Iman Sudjudi pavilion, Gatot Soebroto Army Hospital from February to April were 290 people, 60 of whom had ovarian cancer (21%). The purpose of writing this Scientific Paper is to determine the results of the implementation of nursing care for Mrs. K post Bilateral Hysterectomy Salpingo Oophorectomy (HTSOB) with acute pain nursing problems by taking non-pharmacological actions to fulfill the need for comfort with distraction techniques. This research method is a descriptive method using a case study approach method in patients with stage IIC ovarian cancer post Bilateral Hysterectomy Salpingo Oophorectomy (HTSOB) in the treatment room on the 2nd floor of the dr. Iman Sudjudi Pavilion, Gatot Soebroto Army Hospital. The results of the case study showed that the management of nursing care in post-Hysterectomy Salpingo Oophorectomy Bilateral (HTSOB) patients with acute pain who underwent distraction techniques within a period of 3x24 hours obtained results in a decrease in the intensity of the pain scale before the pain scale was 6 and after it became a pain scale of 2. The resulting nursing evaluation was that the goal was achieved, some problems had not been resolved